THE PROBLEMS OF IMPLEMENTING THE FEDERAL STATE EDUCATIONAL STANDARDS RELATED TO THE SECONDARY VOCATIONAL EDUCATION - B. I. Shemet; O. B. Shemet (Образование и наука)
The paper considers the inner problems of secondary vocational education, activated by implementation of the new competence oriented educational standards. The comprehension of the multi-dimensional construct of professional competence along with the related delusions is regarded as one of the problems. According to the authors, teachers are supposed to know the methods, educational content and objectives of teaching activity, while the students have to understand what they study and why. The authors argue that the task of competence formation can’t be carried out only by means of reproductive methods. There is an urgent need for adapting the theory of developmental education to the specifics of vocational training. The authors insist on further studies for finding the optimum solutions of the given problems, otherwise the Federal State Educational Standards are unlikely to facilitate the quality assurance of secondary vocational education.